2021
DOI: 10.1590/1414-431x2021e11353
|View full text |Cite
|
Sign up to set email alerts
|

Renal fibrosis due to multiple cisplatin treatment is exacerbated by kinin B1 receptor antagonism

Abstract: Cisplatin is a widely used chemotherapeutic drug, but its side effects are a major limiting factor. Nephrotoxicity occurs in one third of patients undergoing cisplatin treatment. The acute tubular injury caused by cisplatin often leads to a defective repair process, which translates into chronic renal disorders. In this way, cisplatin affects tubular cells, and maladaptive tubules regeneration will ultimately result in tubulointerstitial fibrosis. Kinins are well known for being important peptides in the regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Administration of R-715 has been demonstrated to elevate endothelin-1 levels, resulting in heightened renal fibrosis. Budu et al, observed that deletion and antagonism of B1R did not lead to increased macrophages, thereby preventing the transition from M1 to M2 polarization [ 131 ]. Although this intervention offers acute protection, it may induce maladaptive tubular regeneration and mild toxicity, exacerbating renal fibrosis.…”
Section: Macrophages (M1/m2) Plasticity and Regulation In Clinical Re...mentioning
confidence: 99%
“…Administration of R-715 has been demonstrated to elevate endothelin-1 levels, resulting in heightened renal fibrosis. Budu et al, observed that deletion and antagonism of B1R did not lead to increased macrophages, thereby preventing the transition from M1 to M2 polarization [ 131 ]. Although this intervention offers acute protection, it may induce maladaptive tubular regeneration and mild toxicity, exacerbating renal fibrosis.…”
Section: Macrophages (M1/m2) Plasticity and Regulation In Clinical Re...mentioning
confidence: 99%